Museu Histórico em Campina Grande: ação político-cultural do patrimônio e da memória (1980-1983) - Macêdo, Vanessa Costa de (2012)
The main objective of this dissertation is to discuss the processes involved in the establishment of the Historical Museum of Campina Grande (Museu Histórico de Campina Grande, or MHCG) between the years of 1980 to 1983. It was in these years that occurred the promulgation of the law which enabled the creation of the Department of Cultural Heritage and the inauguration of the museum, which was one of the actions of the department. We seek to establish three conditions and possibilities which enabled the creation of the museum: the political-cultural demand which were established by the government organs of the historical heritage subsided by the National Pro-Memory Foundation (Fundação Nacional Pró-Memória Pró-Memória), a heritage action; the demand of a group of intellectuals, responsible for the Geografical and Historical Institute of Campina Grande, of maintaining the historical memory of the city; the forefront intellectual actions of William Ramos Tejo, responsible for the creation of the MHCG and director of the Department of Cultural Heritage in its initial years. Our objective is to determine the importance of each of these conditions in the museum project, which establishes the directives and possibilities of the museum actions. Based on these three conditions, we also seek to argue the discursive practice which opens way to establish the historical narrative which exists because of the expositions of the MHCG on the history of Campina Grande. Such discursive practice can also be seen as an educational action of the intellectual society on the acknowledgement the official memory. With this work, we seek to help on the recreation of the context of the patrimonial heritage actions of the city as it was enabled by the Department of Cultural Heritage in 1980. We emphasize the need of a historical argument on the places which promote the memory of the city, reconfiguring these based on the actions regarding the demands of the heritage action established by local agents. In summary, we compose a study which seeks to understand the implantation of such practices in a local level.